2022
DOI: 10.1111/ijpo.12890
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration in BMI gain following COVID‐19 restrictions. A longitudinal study with 7‐ to 10‐year‐old primary school children

Abstract: Background: The ramifications of COVID-19 restrictions might accelerate the already rising proportion of children with overweight or obesity. Objectives: To assess the association between COVID-19 restrictions and changes in body mass index (BMI) and the proportion of children with overweight or obesity. Methods: Cohort study with baseline measurements in September 2019 (prior to COVID-19 restrictions) and follow-up in June 2020, September 2020, and March 2021 at 12 primary schools in Austria. The height and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
8
25
1
Order By: Relevance
“…Consistent with our findings, there are already a number of studies reporting increases in BMI associated with the COVID-19 pandemic [ 16 , 19 , 20 , 23 , 44 , 45 , 46 ], but few studies [ 17 , 22 ] have objectively measured health-related fitness in a representative sample, and our study is the first scientific report to present results from the period prior to COVID-19, as well as from a 2-year follow-up period as the pandemic ran its course.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our findings, there are already a number of studies reporting increases in BMI associated with the COVID-19 pandemic [ 16 , 19 , 20 , 23 , 44 , 45 , 46 ], but few studies [ 17 , 22 ] have objectively measured health-related fitness in a representative sample, and our study is the first scientific report to present results from the period prior to COVID-19, as well as from a 2-year follow-up period as the pandemic ran its course.…”
Section: Discussionsupporting
confidence: 92%
“…The restrictions caused by the COVID-19 pandemic had an equally significant impact on the health and fitness of children and adolescents [ 15 , 16 , 17 ]. In particular, cardiorespiratory fitness (CRF), which is a strong health maker [ 18 ], and changes in body mass index (BMI) showed dramatic negative trends due to the COVID-19 restrictions [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the beginning of the worldwide COVID-19 pandemic and the associated restrictions on physical activity and temporary bans (mostly during lockdown phases) on organized sports in general and in schools, the already serious obesity pandemic underwent a worrisome acceleration [ 37 , 38 , 39 , 40 , 41 ] and health-related fitness scores showed dramatic decreases [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that boys, unlike girls, continued gaining weight although lockdown measurements were eased. Boys also were more susceptible to weight gain during lockdown in studies in Austrian [40] and Chinese children [22,41] and Italian adolescents with obesity [35].…”
Section: Discussionmentioning
confidence: 99%